Plasma Fatty Acids in Zambian Adults with HIV/AIDS: Relation to Dietary Intake and Cardiovascular Risk Factors. (26th May 2015) - Nyirenda, Christopher K.; Kabagambe, Edmond K.; Koethe, John R.; Kiage, James N.; Chi, Benjamin H.; Musonda, Patrick; Blevins, Meridith; Bosire, Claire N.; Tsai, Michael Y.; Heimburger, Douglas C.
Abstract : Objective . To determine whether 24 hr dietary recalls (DR) are a good measure of polyunsaturated fatty acid (PUFA) intake when compared to plasma levels, and whether plasma PUFA is associated with markers of HIV/AIDS progression and cardiovascular disease (CVD) risk. Methods . In a cross-sectional study among 210 antiretroviral therapy-naïve HIV-infected adults from Lusaka, Zambia, we collected data on medical history and dietary intake using 24 hr DR. We measured fatty acids and markers of AIDS progression and CVD risk in fasting plasma collected at baseline. Results . PUFA intakes showed modest correlations with corresponding plasma levels; Spearman correlations were 0.36 ( p < 0.01 ) for eicosapentaenoic acid and 0.21 ( p = 0.005 ) for docosahexaenoic acid. While there were no significant associations ( p > 0.05 ) between total plasma PUFA and C-reactive protein (CRP) or lipid levels, plasma arachidonic acid was inversely associated with CRP and triglycerides and positively associated with HDL-C, CD4+ T-cell count, and plasma albumin ( p < 0.05 ) . Plasma saturated fatty acids (SFA) were positively associated with CRP ( β = 0.24; 95% CI: 0.08 to 0.40, p = 0.003 ) and triglycerides ( β = 0.08; 95% CI: 0.03 to 0.12, p < 0.01 ). Conclusions . Our data suggest that a single DR is inadequate for assessing PUFA intake and that plasma arachidonic acid levels may modulate HIV/AIDS progression and CVD risk.